ANALISIS MISKONSEPSI MATERI PADA BUKU PEMBELAJARAN BIOLOGI KELAS VII SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO TAHUNPEMBELAJARAN 2022/2023 - Waoma, Wilianis Monika (Universitas Nias Raya, 2023)
Misconception is a concept that is not in accordance with the actual concept. Misconceptions can also be interpreted as initial concepts that are not in accordance with scientific truths. The aim of this research is to find out the Misconceptions of Material in Class VII Biology Learning Books at SMP Negeri 1 Luahagundre Maniamolo for the 2022/2023 Academic Year. The type of research used in this study is a type of qualitative research with a descriptive approach by conducting reference studies. Collecting data in this study is by giving tests and through direct interviews both with teachers and with students. Data analysis used in the form of data collection, data reduction, and data presentation. The results of this study are as follows: (1) Students lack the ability to understand the material being studied so that it creates many misconceptions about the material being studied, (2) The learning resources that will be studied by these students are still limited so that the mindset students in learning material do not develop), (3) (the learning model that subject teachers are exposed to is still conventional so that it does not attract students' interest in the teaching and learning process and (4) Assignment of assignments but not accompanied by further discussion of the concepts or answers given correctly from the task, so that it can lead to misconceptions in students). As for the suggestions in this study are as follows (1) It is hoped that the relevant agencies are more observant in choosing textbooks used by students so that misconceptions do not occur. Teachers should analyze and find out the misconceptions from the books they will teach students. (2) Teachers are expected to be able to provide references to other sources for student learning and are not fixated on one textbook source. (3) Textbook authors can avoid these misconceptions by providing examples of simpler and contextual analogies, as well as simplifying sentences that help students understand the concepts to be conveyed.